2007
DOI: 10.1590/s0100-204x2007000500018
|View full text |Cite
|
Sign up to set email alerts
|

Body condition score to predict the postpartum fertility of crossbred beef cows

Abstract: -The relationship between changes in body condition score (BCS) during the postpartum and fertility in beef cows suckling calves under extensive conditions were investigated. Cows were subjected to four BCS evaluations over the postpartum period, starting around one month after calving. In the second evaluation cows were treated with medroxy-progesterone acetate impregnated pessaries and received an injection of estradiol benzoate. At the third evaluation, pessaries were removed and calves were separated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
(2 reference statements)
1
7
0
7
Order By: Relevance
“…The lowest values of BCS were recorded in the month of October. Our findings are in agreement with Chacon et al (1999); Moraes et al (2007); Ndlovu and Muchenje (2009), who found that seasonal changes were associated with BCS in the tropical regions of Costa Rica, Brazil and South Africa respectively. Chacon et al (1999) found higher values during the period of January to May and then BCS values started to decrease in June.…”
Section: Resultssupporting
confidence: 93%
“…The lowest values of BCS were recorded in the month of October. Our findings are in agreement with Chacon et al (1999); Moraes et al (2007); Ndlovu and Muchenje (2009), who found that seasonal changes were associated with BCS in the tropical regions of Costa Rica, Brazil and South Africa respectively. Chacon et al (1999) found higher values during the period of January to May and then BCS values started to decrease in June.…”
Section: Resultssupporting
confidence: 93%
“…Percentage for G2 was similar to that described for zebu cattle by , with pregnancy rates between 45% and 67% and by Ereno et al (2007) between 50% and 54%. It was also similar to crossbreed cows in Moraes et al (2007) Progestagen (IPRD) associated with estradiol benzoate (EB) was employed in the two experimental groups, following reports by Moreira et al (2000) who described variations in the tested hormonal protocols. There was a greater synchronization of follicle emergence when EB was applied on the first day of treatment, coupled to 30mg progesterone exclusively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Se o número de novilhas for suficiente para suprir a reposição, todas as vacas sem cia ao pé são descartadas, caso contrário, fica no rebanho um número suficiente para suprir o déficit de novilhas. Com a DPAR, PN, GMDND e DDESM, o modelo calcula o peso ao desmame dos bezerros, O escore de condição corporal (ECC) ou condição corporal é uma medida subjetiva de gordura corporal e a escala adotada nesse trabalho é a de 1 a 5 (segundo Moraes et al 2005), de modo que 1= animal muito magro e 5 = animal gordo).…”
Section: Methodsunclassified